Achilles tendon xanthomas are associated with the presence and burden of subclinical coronary atherosclerosis in heterozygous familial hypercholesterolemia: A pilot study. (August 2017) - Mangili, Leonardo C.; Miname, Marcio H.; Silva, Pamela R.S.; Bittencourt, Marcio S.; Rocha, Viviane Z.; Mangili, Otavio C.; Salgado Filho, Wilson; Chacra, Ana P.; Jannes, Cinthia E.; Pereira, Alexandre C.; Santos, Raul D.
Abstract: Background and aims: Achilles tendon xanthomas (ATX) are a sign of long-term exposure to high blood cholesterol in familial hypercholesterolemia (FH) patients, which have been associated with cardiovascular disease. We evaluated the ATX association with the presence and extent of subclinical coronary atherosclerosis in heterozygous FH patients. Methods: 102 FH patients diagnosed by US-MEDPED criteria (67% with genetically proven FH), with median LDL-C 279 mg/dL (interquartile range: 240; 313), asymptomatic for cardiovascular disease, underwent computed tomography angiography and coronary artery calcium (CAC) quantification. Subclinical coronary atherosclerosis was quantified by CAC, segment-stenosis (SSS) and segment-involvement (SIS) scores. Adjusted Poisson regression was used to assess the association of ATX with subclinical atherosclerosis burden as continuous variables. Results: Patients with ATX (n = 21, 21%) had higher LDL-C and lipoprotein(a) [Lp(a)] concentrations as well as greater CAC scores, SIS and SSS ( p  < 0.05). After adjusting for age, sex, smoking, hypertension, previous statin use, HDL-C, LDL-C and Lp(a) concentrations, there was an independent positive association of ATX presence with CAC scores (β = 1.017, p  < 0.001), SSS (β = 0.809, p  < 0.001) and SIS (β = 0.640, p  < 0.001). Conclusions: ATX are independently associated with the extension of subclinical coronary atherosclerosis quantified by tomographic scores in FH patients. Highlights: Familial hypercholesterolemia is associated with Achilles tendon xanthomas. Achilles tendon xanthomas mark lifelong exposure to high blood cholesterol. Achilles tendon xanthomas were associated with severity of coronary calcification. Achilles tendon xanthomas were associated with coronary plaque burden.